2007
DOI: 10.1111/j.1708-8208.2007.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Metastasis around Dental Implants: A Case Report

Abstract: Optimal clinical examination in conjunction with radiography and histopathology is a necessity in order to discover malignant lesions in time. Routine dental check-ups must comprise more thorough soft-tissue examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 11 publications
0
54
0
Order By: Relevance
“…Fourth, most of the previous cases described as metastases to the oral region from a lung carcinoma consisted of male patients. Metastasis around dental implants has been reported before (2). Local factors have an influence on the growth of metastasis; trauma has been observed to facilitate the growth of blood-borne metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Fourth, most of the previous cases described as metastases to the oral region from a lung carcinoma consisted of male patients. Metastasis around dental implants has been reported before (2). Local factors have an influence on the growth of metastasis; trauma has been observed to facilitate the growth of blood-borne metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…In a review of 114 cases of metastatic jaw tumors, D'Silva et al (1) found that the most common jaw symptom was pain. Other signs and symptoms included swelling, presence of intraoral mass, loose or extruded teeth, cortical expansion, regional lymphadenopathy, gum irritation, ulceration, exophytic growth, halitosis, numbness or paresthesia of the lower lip, and trismus (4,(7)(8)(9). Special attention should be given to patients with numb-chin syndrome or mental nerve neuropathy, a symptom that should always raise the suspicion of a metastatic disease in the mandible (5).…”
Section: Discussionmentioning
confidence: 99%
“…M alignant tumors metastatic to the oral cavity are uncommon, comprising about 1% of newly diagnosed oral malignancies (1)(2)(3)(4). They most commonly involve the jawbones, and mandible is the most common site of involvement (2,3,5).…”
mentioning
confidence: 99%
“…Tumorigenesis of jaw bone is usually the result of metastasis of cancer originally derived from breast [7], lung [8] as well as prostate [9], as previously reported. To our knowledge, no report has been found about the jaw metastasis of cancer originating from thymus, which is extremely rare in clinical practice.…”
Section: Discussionmentioning
confidence: 99%